2022
DOI: 10.26508/lsa.202201506
|View full text |Cite
|
Sign up to set email alerts
|

Dlk1-Dio3 cluster miRNAs regulate mitochondrial functions in the dystrophic muscle in Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a severe muscle disease caused by impaired expression of dystrophin. Whereas mitochondrial dysfunction is thought to play an important role in DMD, the mechanism of this dysfunction remains to be clarified. Here we demonstrate that in DMD and other muscular dystrophies, a large number of Dlk1-Dio3 clustered miRNAs (DD-miRNAs) are coordinately up-regulated in regenerating myofibers and in the serum. To characterize the biological effect of this dysregulation, 14 DD-miRNAs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This is consistent with Pokharel et al [28] who also detected similar miRNAs in the same clustered locus. This miRNA cluster is highly conserved among placental mammals and known to be regulated by a maternally imprinted DLK1-DIO3 region, which has been associated with severe muscle disease caused by impaired expression of dystrophin called Duchenne muscular dystrophy [33][34][35]. Additionally, two growth QTL associated with sheep body weight [36] and average daily gain [37] were found coinciding with the miRNA cluster on OAR18.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with Pokharel et al [28] who also detected similar miRNAs in the same clustered locus. This miRNA cluster is highly conserved among placental mammals and known to be regulated by a maternally imprinted DLK1-DIO3 region, which has been associated with severe muscle disease caused by impaired expression of dystrophin called Duchenne muscular dystrophy [33][34][35]. Additionally, two growth QTL associated with sheep body weight [36] and average daily gain [37] were found coinciding with the miRNA cluster on OAR18.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with Pokharel et al [ 38 ], who also detected similar miRNAs in the same clustered locus. This miRNA cluster is highly conserved among placental mammals and is known to be regulated by a maternally imprinted DLK1-DIO3 region, which has been associated with severe muscle disease, which is caused by the impaired expression of dystrophin called Duchenne muscular dystrophy [ 43 , 44 , 45 ]. Additionally, two growth QTLs associated with sheep body weight [ 46 ] and average daily gain [ 47 ] were found to coincide with the miRNA cluster on OAR18.…”
Section: Discussionmentioning
confidence: 99%
“…This mammalian-specific ncRNA locus has evolved to encode three different classes of ncRNAs, each harboring multiple copies, that are transcribed simultaneously. To date, studies have largely focused on investigating portions of the gene including deletions of selected miRNA sub-clusters, or misexpression of its individual ncRNAs, which have resulted in overlapping but largely distinct phenotypes (Kameswaran et al, 2014; Labialle et al, 2014; Qian et al, 2016; Vu Hong et al, 2022; Wust et al, 2018). Our results differ in two key respects from prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…The imprinted Dlk1-Dio3 ncRNA gene, encoding over 60 microRNAs (miRNAs), several long noncoding RNAs (lncRNAs), and a group of small nucleolar RNAs (snoRNAs), has emerged as a candidate regulator of metabolism and cell state. Expression levels of Dlk1-Dio3 ncRNAs have been shown to correlate with changes in metabolic activity, including mitochondrial pathways, in the hematopoietic, pancreatic, and muscle lineages (Kameswaran et al, 2014; Labialle et al, 2014; Qian et al, 2016; Vu Hong et al, 2022; Wust et al, 2018). In addition, we previously reported that Meg3 , a major lncRNA in this locus, regulates myoblast plasticity, but also noted mitochondrial defects in Meg3 -deficient cells (Dill et al, 2021).…”
Section: Introductionmentioning
confidence: 99%